2016
DOI: 10.3390/f7070137
|View full text |Cite
|
Sign up to set email alerts
|

Ponderosa Pine Forest Restoration Treatment Longevity: Implications of Regeneration on Fire Hazard

Abstract: Abstract:Restoration of pine forests has become a priority for managers who are beginning to embrace ideas of highly heterogeneous forest structures that potentially encourages high levels of regeneration. This study utilizes stem-mapped stands to assess how simulated regeneration timing and magnitude influence longevity of reduced fire behavior by linking growth and yield model outputs to a crown fire prediction model. Treatment longevity was assessed as return time to within 10% of pre-treatment predicted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Even after 50 years, however, mean CBD was far less than pretreatment levels, indicating long-lived resistance to active crown fire (Figure 3). These findings are consistent with recent work that also showed long-lived reduction in CBD following treatments such as those simulated here, translating to prolonged reductions in the potential for active crown fire [20]. Treated stands in the Douglas-fir cover type did experience an~10% increase in CBD per decade compared to only a slight increase over the simulation period for ponderosa pine-dominated stands, which we attribute to the systematic differences in composition, productivity and tree regeneration rates between cover types in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Even after 50 years, however, mean CBD was far less than pretreatment levels, indicating long-lived resistance to active crown fire (Figure 3). These findings are consistent with recent work that also showed long-lived reduction in CBD following treatments such as those simulated here, translating to prolonged reductions in the potential for active crown fire [20]. Treated stands in the Douglas-fir cover type did experience an~10% increase in CBD per decade compared to only a slight increase over the simulation period for ponderosa pine-dominated stands, which we attribute to the systematic differences in composition, productivity and tree regeneration rates between cover types in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Because most of the simulated landscape was untreated, this ultimately resulted in all simulations showing a decrease in fire size, mean rate of spread, and active and passive crown fire proportions through time (Figure 5a,b and Figure 6). These findings are consistent with the outcomes of similar studies conducted in dry forest types in California and contribute to a growing body of literature that suggests a better understanding of crown recession is critical for improving our ability to predict the longevity of fuel treatment effects [20,60,61]. These studies also highlight the importance of accounting for stand dynamics in untreated areas when assessing the longevity of treatment effects for project areas that include many stands.…”
Section: Assumptions and Limitationssupporting
confidence: 84%
See 1 more Smart Citation
“…, Tinkham et al. ), or (4) local feedbacks between fire weather, topography, and fuels. A previous study found that both an extended time since previous fire and the occurrence of extreme fire behavior were associated with moderate to high‐severity fire in the Rim Fire (Lydersen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Various natural disturbance processes of forest ecosystems have dramatic impacts on the structure of western coniferous forests, particularly fire and bark beetles (Tinkham et al 2016). These disturbances can significantly alter floral resource availability, which has a corresponding impact on bee pollinators.…”
Section: Presented By Seth Davismentioning
confidence: 99%